2017
DOI: 10.26719/2017.23.6.404
|View full text |Cite
|
Sign up to set email alerts
|

The relation between pica and iron deficiency in children in Zanjan, Islamic Republic of Iran: a case-control study

Abstract: Lien entre le pica et les carences en fer chez les enfants à Zanjan, République islamique d'Iran : étude castémoinRÉSUMÉ La présente étude cas-témoin avait pour objectif de déterminer la fréquence du pica et son lien avec les carences en fer chez les enfants de Zanjan. Nous avons sélectionné 872 enfants de manière aléatoire et déterminé la fréquence du pica. Nous avons choisi des élèves en bonne santé du même âge, sexe et de la même classe que nos cas afin de servir de groupe témoin. Les cas et les témoins ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
6
2
Order By: Relevance
“…Conversely, the prevalence of pica in our study was much higher than that reported among children in Ghana (9.1%) [ 6 ], Iran (6.7%) [ 7 ], Switzerland (10.0%) [ 8 ], Germany (12.3%) [ 16 ], Nepal (12.5%) [ 17 ], and France (0%) [ 32 ]. It should be noted that it could be difficult to assess the actual/true prevalence of pica because its definition varies, different methods are used to collect data, and some people may not report practicing pica or even do it secretly [ 19 ].…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Conversely, the prevalence of pica in our study was much higher than that reported among children in Ghana (9.1%) [ 6 ], Iran (6.7%) [ 7 ], Switzerland (10.0%) [ 8 ], Germany (12.3%) [ 16 ], Nepal (12.5%) [ 17 ], and France (0%) [ 32 ]. It should be noted that it could be difficult to assess the actual/true prevalence of pica because its definition varies, different methods are used to collect data, and some people may not report practicing pica or even do it secretly [ 19 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Our results showed that females had a 3.5 times higher risk of pica, consistent with previous reports showing that geophagy was more prevalent in girls (80.2%) than in boys 67.7%) in Zambia [ 14 ]. Conversely, a previous study showed no significant difference in gender and pica prevalence in Iran [ 7 ] and Germany [ 13 ]. In the current study, a lower level of father’s education was associated with pica (AOR = 2.05).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies conducted by Shruti et al 25 and Gupta et al 26 also reported a statistically significant association between pica and IDA (p < 0.5). However, Sadeghzadeh et al did not find any association between pica and anaemia and/or iron deficiency (p > 0.05) 27 . This might be because pica is more a cultural behaviour than a result of iron deficiency.…”
Section: Discussionmentioning
confidence: 92%
“…Its prevalence in Iran was reported in a case study at 6.5%, of which 63.2% were girls and 36.8% were boys. Soil and paper were the most common types of pica craving in this study (Sadeghzadeh et al, 2017).…”
mentioning
confidence: 74%